Alteration of Hepatic and Renal Biomarkers Among Libyan Smokers - Sanaa Ramadan Aljali; Abdounasser Albasher Omar; Manal Khalifa Hasan; Rayan Albasheer Abu Salama; Alaa Dow Attahhar; Salma Abdularahman Hmeid; Eman Abdulfatah Aleisawie (African Journal of Advanced Pure and Applied Sciences, 2024)
Smoking, a risky habit, harms human body organs and alters the levels of different blood parameters. This study aimed to assess the effect of smoking on kidney and liver function tests in Libya. Thirty-one smoker residents in Gharyan, Libya, with an age range of 20–60 years, were recruited. the serum levels of creatinine, urea, ALP, AST, and ALT were measured. Values outside the reference intervals were recorded for all three enzymes (ALP, ALT, and AST) related to liver functions. In contrast, in the case of the kidney, values outside the reference interval were recorded for creatinine only, and no values outside the reference interval were recorded for urea. In conclusion, the smoking effect was greater on the liver of smokers than on the kidneys. Smokers should be aware that smoking is harmful to their health and it causes liver and kidney damage.